Cyanobacteria in Sulfidic Spring Microbial Mats Can Perform Oxygenic and Anoxygenic Photosynthesis Simultaneously during an Entire Diurnal Period - Klatt, Judith M.; de Beer, Dirk; Häusler, Stefan; Polerecky, Lubos (Frontiers in Microbiology, 2016)
We used microsensors to study the regulation of oxygenic and anoxygenic photosynthesis by light and sulfide in a cyanobacterium dominating microbial mats from cold sulfidic springs. Both photosynthetic modes were performed simultaneously over all H2S concentrations (1–2200 µM) and irradiances (4–52 µmol photons m-2 s-1) tested. Anoxygenic photosynthesis increased with H2S concentration while the sum of oxygenic and anoxygenic photosynthetic rates was constant at each light intensity. Thus, the total photosynthetically driven electron transport rate was solely controlled by the irradiance level. The partitioning between the rates of these two photosynthetic modes was regulated by both light and H2S concentration. The plastoquinone pool (PQ) receives electrons from sulfide:quinone:reductase (SQR) in anoxygenic photosynthesis and from photosystem II (PSII) in oxygenic photosynthesis. It is thus the link in the electron transport chain where both pathways intersect, and the compound that controls their partitioning. We fitted our data with a model of the photosynthetic electron transport that includes the kinetics of plastoquinone reduction and oxidation. The model results confirmed that the observed partitioning between photosynthetic modes can be explained by a simple kinetic control based on the affinity of SQR and PSII towards PQ. The SQR enzyme and PSII have similar affinities towards PQ, which explains the concurrent oxygenic and anoxygenic photosynthesis over an astonishingly wide range of H2S concentrations and irradiances. The elegant kinetic control of activity makes the cyanobacterium successful in the fluctuating spring environment. We discuss how these specific regulation mechanisms may have played a role in ancient H2S-rich oceans.